2020
DOI: 10.1017/ppr.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for Upland Occupation in the Mesolithic of Scotland

Abstract: This paper discusses the evidence for periodic human activity in the Cairngorm Mountains of Scotland from the late 9th millennium to the early 4th millennium cal bc. While contemporary paradigms for Mesolithic Europe acknowledge the significance of upland environments, the archaeological record for these areas is not yet as robust as that for the lowland zone. Results of excavation at Chest of Dee, along the headwaters of the River Dee, are set into a wider context with previously published excavations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Certainly, the archaeological evidence increasingly does not support the view that hunter-gatherers disappeared from the British landscape swiftly and without trace. On the basis of chronological modelling, Griffiths (2014, 24) has demonstrated that groups pursuing Mesolithic and Neolithic lifeways continued to exist alongside each other for some centuries in northern England, and there are suggestions that this may have been the case in other parts of Britain as well (Elliott & Griffiths 2018, 357; Wickham-Jones et al 2020, 36). In Wiltshire, Gron et al (2018) argue that the distinctive deposits in the large pit known as the Coneybury Anomaly resulted from coordinated activities on the part of groups of hunters and farmers during the thirty-eighth century bc , three centuries after the start of the Neolithic.…”
Section: Rates Of Changementioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the archaeological evidence increasingly does not support the view that hunter-gatherers disappeared from the British landscape swiftly and without trace. On the basis of chronological modelling, Griffiths (2014, 24) has demonstrated that groups pursuing Mesolithic and Neolithic lifeways continued to exist alongside each other for some centuries in northern England, and there are suggestions that this may have been the case in other parts of Britain as well (Elliott & Griffiths 2018, 357; Wickham-Jones et al 2020, 36). In Wiltshire, Gron et al (2018) argue that the distinctive deposits in the large pit known as the Coneybury Anomaly resulted from coordinated activities on the part of groups of hunters and farmers during the thirty-eighth century bc , three centuries after the start of the Neolithic.…”
Section: Rates Of Changementioning
confidence: 99%
“…It has sometimes been suggested that the later Mesolithic communities of Britain were not only isolated, but sparsely distributed and culturally impoverished (see, for example, Miles 2016). In all probability there was considerable variation in patterns of settlement, mobility and subsistence during this period (Preston & Kador 2018), although a picture of very numerous small sites that had been repeatedly returned to is quite widespread throughout much of Britain, in a variety of different environments (Champness 2014; Simmonds et al 2019, 52; Waughman 2017, 12; Wickham-Jones et al 2020). However, there are also sites like Stainton West in Cumbria (Brown 2021) and Blick Mead in Wiltshire (Jacques & Phillips 2014, 24), which attest dense accumulations of population and appreciable logistical sophistication.…”
Section: Timing and Continuitymentioning
confidence: 99%
“…By the time of Mesolithic settlement in the early 8th millennium bc, therefore, local deciduous woodland had altered the landscape of the lower Dee Valley (Illus 4.10), in contrast with the evidence for pine forests higher into the Cairngorms (Paterson 2011;Wickham-Jones et al 2020). Open canopy birch and hazel woodland was recorded during the excavation of an early 8th-millennium bc site at Warren Field, Crathes (Davies et al 2009;Tipping in Dingwall et al 2019b: 30-7).…”
Section: Climate Vegetation and Landscapementioning
confidence: 99%
“…Many syntheses of Mesolithic settlement throughout Europe have established a relation to river valleys, whether it be a simple association with proximity to water (Masojć 2007) or through detailed multi-proxy environmental reconstruction to more specific micro-environments (Berger et al, 2016;Bos and Urz, 2003;Bos et al, 2006;Donahue and Lovis, 2006;Jochim, 2011;Passmore and Waddington, 2012, 128, 130;Ramsden et al, 1995;Vandenberghe et al 2010;Weerts et al, 2012;Wickham-Jones et al, 2020). In northern Britain, the large and long river systems like that of the Tweed (Mulholland, 1970;Passmore and Waddington, 2012) are seen to have been routeways to the interior as well as resource-rich and favourable to settlement.…”
Section: Introductionmentioning
confidence: 99%